A Comparative Review of Sex Education and Medical Interventions in STI Prevention - Arwan (Yayasan Sinergi Kawula Muda, 2023)
Sexually transmitted infections (STIs) remain a major global public health concern, particularly among young populations. Comprehensive sex education has been identified as a key strategy for reducing STI incidence, improving awareness, and promoting safe sexual behaviors. This study examines the effectiveness of sex education compared to abstinence-only approaches and public health campaigns, analyzing its role in behavioral change and stigma reduction. A systematic review of peer-reviewed literature from major academic databases, including PubMed, Scopus, and Google Scholar, was conducted. The findings reveal that sex education programs integrated into national curricula significantly improve STI prevention outcomes. Compared to abstinence-based programs, comprehensive sex education leads to higher rates of contraceptive use and better decision-making regarding sexual health. Moreover, its role in reducing stigma fosters an environment where individuals feel encouraged to seek healthcare services and undergo STI testing without fear of discrimination. Despite its effectiveness, sociocultural barriers and inconsistent policy implementation continue to hinder sex education initiatives. Addressing these challenges requires interdisciplinary collaboration between educators, healthcare professionals, and policymakers. Future research should explore long-term impacts, digital education tools, and culturally adaptive strategies to enhance program efficacy. Strengthening sex education policies will be crucial for reducing STI prevalence and improving global sexual health outcomes.